Disciplinary cases of Filipino teachers in the late 19th century - Concepcion, Grace Liza Y. (2014)
This paper discusses a number of archival records of disciplinary cases involving Filipino teachers in the 19th century. These cases were handled by the Spanish Superior Commission on Primary Education. The study of these documents sheds light not only on the government’s concerns about educational reform but also shows the relationships among the community members and their stake in primary education. The study yields abundant information on how Filipino teachers negotiated the colonial system. It is thus a window that gives a view of Philippine social history.

The researcher examined 41 records dating from 1877 to 1893. These records are found in the Philippine Province Archive of the Society of Jesus. Other related records are filed among the digitized documents of the Philippine National Archives housed at present in the Unidad de Tratamientos Archivisticos in the offices of the Consejo Superior de Investigaciones Científicas in Madrid. The author consulted both archives. Some records contain only summaries of the disciplinary cases based on the teachers’ dossiers. Others include the teachers’ full records and proceedings of the disciplinary cases. Although the records that were studied for this research are incomplete, they are so varied and voluminous that the handling of disciplinary cases of teachers can be reconstructed. They are an eloquent evidence of the challenges that the colonial government faced in the implementation of the ideals that supported the Royal Decree on Primary Education of 1863, the law that aimed to provide elementary education on a nationwide scale. In a way, these cases also indicate Filipinos’ attitudes towards these educational reforms.
Keywords: Catholic Church -- Education -- Philippines; Philippines -- History -- Spanish regime, 1521-1898; Teachers -- Discipline -- History -- 19th century